Wetland degradation diagnosis and zoning based on the integrated degradation index method. (1st May 2022) - Chen, Kexin; Cong, Pifu; Qu, Limei; Liang, Shuxiu; Sun, Zhaochen
Abstract: With the immense disturbance of human activities, the wetlands all over the world have been degrading. It is urgent to evaluate the degree of degradation and determinate the degraded areas. This paper used satellite images of the Yellow River Delta in 1976, 1996, and 2016, and the kilometer grid was used as the research unit. From the landscape transition matrix, landscape connectivity, and hydrological connectivity three aspects, the wetland degradation diagnosis index system was constructed by selecting the seven indices. Wetland degradation diagnosis and zoning were studied by the integrated degradation index and Global autocorrelation. The study found the degree of degeneration has increased for 40 years. The degraded areas were classified into 5 levels according to the degree of degradation: undegraded, light, moderate, severe, and extreme. The degraded areas were positively clustered in space. From 1976 to 2016, the extremely degraded areas were concentrated in coastal areas and the severely degraded areas tended to expand from inland to sea. In 1996, the global Moran Index was 0.90, and the severely degraded areas were mainly concentrated in the central region, accounting for 13.31%. In 2016, the global Moran Index was 0.88, and the severely degraded areas were mainly concentrated in the central region, accounting for 21.64%. The main focus of the moderately degraded areas was the new estuary, accounting for 15.44%. In the future, management departments need to strengthen the management of the new estuary and coastal areas to prevent further degradation. Graphical abstract: Image 1